Applications of Methodology of Calculation of the Number of Connections (MCNC) in Solving Transport Attendance - Gogola, Marian (Communications - Scientific letters of the University of Zilina, 2005)
This paper deals with the new MCNC (Methodology of Calculation of the Number of Connections) which is focused on the problem of transport attendance in the Zilina county. Starting from the calculation of passenger demands, social-economic parameters and the resulting calculation of the modal split, the allocation of vehicle schedule into an optimisation matrix is modelled. In the last step, the MCNC algorithm calculates a number of connections to achieve optimisation. This methodology can be used with other methodologies to find a better solution for transport attendance, to find a better solution for integration of the transport system. It is also possible to use the MCNC as additional methodology to calculate economic efficiency of the transport system.